Editorial: Bridging Boundaries: Advancing Learning Through Scholarship in An Evolving Academic Landscape - Thomas D. Dyer; Jenny Kuban (Journal of Scholarly Engagement)
The scholarship of teaching and learning focuses on improving student outcomes by lever- aging research on education, instructional design, and pedagogy (Boyer, 1990). Scholars use analytical frameworks to inform innovative classroom policies and practices that enhance the learning experience and promote student success. The Boyer Model of Scholarship not only pro- motes a student-centered learning approach but also inspires faculty members to engage in research activities that inform best practices in teaching and learning. This model recognizes teaching as a significant form of scholarship that influences student development. However, challenges arise when the scholarship of teaching and learning is not explicitly integrated into institutional research plans and frameworks (Simmons et al., 2021). Teaching- focused faculty often face barriers such as limited funding and a lack of collegial support for their scholarly endeavors, hindering the recognition of SoTL as legitimate research (Simmons et al., 2021).